Determining days to ripen and quality characteristics of tomato (Solanum lycopersicum Mill.) from Kuala Lumpur wholesale market - Che Abd Aziz, Nur Anira Akmal (2015)
The objectives of the study were to determine the days to ripen and quality characteristics of tomato from Kuala Lumpur Wholesale Market. This study was conducted in a randomize complete block design (RCBD) with five replications. Fruits from each box were classified into 4 maturity indices, index 2 (breaker), index 3 (turning), index 4 (pink), index 5 (light red/orange). The fruits were allowed to ripen to full-red stage at ambient temperature in the box. Seven parameters which are ripening period of tomato to full-red stage, skin colour, firmness, soluble solids concentration, titratable acidity, vitamin C, and carotenoid content were measured after fruits were allowed to ripen in an ambient condition. Collected data were analyzed with the analysis of variance (ANOVA) to obtain mean comparison between treatments. The mean were separated by least significant difference (LSD) with significant level of P ≤ 0.05. In the study, the initial maturity indices of the tomato fruits effect the ripening period to full-red stage. The tomato skin colour, pulp firmness, soluble solids concentration, titratable acidity, SSC:TA ratio and carotenoid content of the ripened tomato fruits were also significantly affected by the initial maturity stages as fruits ripen to full red-stage. However, there was no significant difference in vitamin C content of fruits ripened from different maturity indices. The ripening periods of tomato fruits ripened from maturity index 2 was the longest period compared to fruits from the maturity indices 3, 4, and 5. Therefore, for commercial ripening, the application of ethylene is recommended for tomato fruits from maturity index 2 to ripen uniformly in short period of time.